The role of discussion boards in a university blended learning program (2011)
Discussion boards as tools in blended English language learning programs have unique characteristics when compared to other synchronous and asynchronous communication tools that are different. Therefore, it is important to investigate the way they operate, their role within a given program and the students’, teachers’ and tutors’ attitudes towards them. This paper contains the report of a study that took place in an English virtual program of a public university in Colombia. Students’ surveys and reflections, the tutor’s and teachers’ interviews and reflections were used to collect data. The results showed the main advantages and disadvantages of the use of the tool as well as ideas for new proposals to improve their use and, therefore, increase the students’ performance in the program.Los foros de discusión, como herramientas en programas de aprendizaje mixto de inglés, tienen características únicas en comparación con otras herramientas sincrónicas y asincrónicas de comunicación. En consecuencia, es importante indagar sobre la forma como funcionan, el papel dentro del programa y las percepciones que tienen los estudiantes, tutores y profesores acerca de ellos. En este artículo se reporta el estudio que se realizó en un programa virtual de inglés de una universidad pública en Colombia, en el primer semestre de 2010. Se recolectó información mediante encuestas y reflexiones de los estudiantes y entrevistas y reflexiones de los profesores. Los resultados muestran las principales ventajas y desventajas en el uso de esta herramienta e ideas para generar nuevas propuestas que mejoren su uso, para así incrementar el desempeño de los estudiantes en el programa.